Corporate Foresight in Multinational Business Strategies - Alexey Bereznoy (Foresight and STI Governance, 2017)
The paper explores corporate foresight as a new important tool within the strategic management system of multinational corporations (MNCs). The author directly connects the recent rise of corporate foresight with MNCs’ growing need to fill the gaps in traditional corporate strategic management, which struggles with the challenges of today’s global turbulent business-environment (known as VUCA world characterised by unprecedented volatility, uncertainty, complexity and ambiguity). From this perspective, corporate foresight is capable of providing a number of viable responses. They include the significant expansion of the horizon of MNCs’ long-term future vision, enhanced capabilities of business-environment scanning (identifying not only clearly visible trends but the so-called weak signals as well) and strengthening intra-firm communications over the course of the strategy development process, thus contributing to the implementation capacity of multinational corporate team. Within the analysis of the actual corporate foresight practices of major multinationals, special attention is paid to the common features of foresight organization (standard process phases, the typical set of methods used) and peculiarities related mainly to different MNCs’ sector-specific environment characteristics, including the complexity and dynamics of change. An attempt is also made to describe the actual impact of corporate foresight activities on the effectiveness of the key functions of MNCs’ strategic management. The author draws the conclusion that corporate foresight is becoming a core element of the strategic management architecture of multinational businesses, striving to protect and strengthen its global market positioning in an increasingly turbulent and unpredictable environment. For MNCs’ top management, trying to find the right strategic course in a radically changing competitive landscape, this powerful tool is increasingly playing the same role as a GPS navigator for car drivers lost in an unfamiliar city.